Prevalence of burnout syndrome among anesthesiologists in the Federal District - Magalhães,Edno (2015)
BACKGROUND: Burnout syndrome is a result of chronic stress, characterized by emotional exhaustion, depersonalization, and a sense of low professional accomplishment. It affects workers under extreme responsibility or those who care for individuals at risk, including anesthesiologists who distanced themselves from the work, patients and colleagues because they feel safer in maintaining indifference. OBJECTIVE: To evaluate the prevalence of burnout syndrome and the intensity of its components and identify the characteristics of those with the syndrome among anesthesiologists in the Federal District. METHOD: A cross-sectional study was carried out with 241 anesthesiologists enrolled in the Society of Anesthesiology of the Federal District. A self-administered questionnaire was used, which included the Maslach Burnout Inventory, demographic, professional, and leisure data. RESULTS: Of the 134 completed questionnaires (55.8%), there was a predominance of male (65.6%), aged 30-50 years (67.9%). Significant lower levels of job satisfaction (47.7%), depersonalization (28.3%), and emotional exhaustion (23.1%) were found. Burnout syndrome showed a prevalence of 10.4%, occurring mainly in men (64.2%), aged 30-50 years (64.2%), with over 10 years of experience (64.2%), working in night shifts (71.4%), sedentary (57.1%), and not taking courses unrelated to medicine (78.5%). Of the participants, 50.7% had at least one of the three criteria to develop the syndrome and only 8.2% have a low risk to manifest it. CONCLUSION: The prevalence of burnout is relevant among anesthesiologists in the Federal District. It is advisable to seek strategies for labor restructuring to reduce stress factors and loss of motivation and increase job satisfaction.